Endometrial stem/progenitor cells and their roles in immunity, clinical application, and endometriosis - Yue Kong; Yang Shao; Chunxia Ren; Gong Yang (Stem Cell Research & Therapy, 2021)
Abstract Endometrial stem/progenitor cells have been proved to exist in periodically regenerated female endometrium and can be divided into three categories: endometrial epithelial stem/progenitor cells, CD140b+CD146+ or SUSD2+ endometrial mesenchymal stem cells (eMSCs), and side population cells (SPs). Endometrial stem/progenitor cells in the menstruation blood are defined as menstrual stem cells (MenSCs). Due to their abundant sources, excellent proliferation, and autotransplantation capabilities, MenSCs are ideal candidates for cell-based therapy in regenerative medicine, inflammation, and immune-related diseases. Endometrial stem/progenitor cells also participate in the occurrence and development of endometriosis by entering the pelvic cavity from retrograde menstruation and becoming overreactive under certain conditions to form new glands and stroma through clonal expansion. Additionally, the limited bone marrow mesenchymal stem cells (BMDSCs) in blood circulation can be recruited and infiltrated into the lesion sites, leading to the establishment of deep invasive endometriosis. On the other hand, cell derived from endometriosis may also enter the blood circulation to form circulating endometrial cells (CECs) with stem cell-like properties, and to migrate and implant into distant tissues. In this manuscript, by reviewing the available literature, we outlined the characteristics of endometrial stem/progenitor cells and summarized their roles in immunoregulation, regenerative medicine, and endometriosis, through which to provide some novel therapeutic strategies for reproductive and cancerous diseases.